Economic evolution in the digital age: assessing the influence of digital transformation and energy consumption on sustainable development - Muneer, Saqib; Singh, Ajay; Tripathi, Abhishek (Frontiers in Human Dynamics, 2025)
Sustainable development has been a fundamental component of long-term economic policies of resource-dependent nations, such as Saudi Arabia and the UAE. This study looks at how digital transformation, foreign direct investment, and energy use interact and affect sustainable development (SD) in two countries from 2000 to 2023. Utilizing sophisticated econometric techniques, including FMOLS, Johansen Co-integration, and Dumitrescu-Hurlin panel causality tests, the findings indicate that digital transformation and Foreign Direct Investment (FDI) exert a positive and substantial influence on sustainable development over the long term. Digital transformation (DT) significantly impacts the integration of technology to attain sustainability objectives. On the other hand, the impact on sustainable development is less significant, with several cases showing a statistically minor causal influence on energy consumption. The causality results reveal a mutual relationship between DT and SD in environmental policy and energy behavior. FDI directly causes SD but is also affected by SD, indicating their interdependence. However, FDI and DT do not show a causal relationship, and FDI Granger causes EU, while the reverse does not. The system remains closely coupled with energy, digital, and investment systems, contributing jointly to sustainable development pathways. These findings provide a valuable framework for governments aiming to foster sustainable growth in the digital realm via improved local technological advancement, effective foreign technical investment, and energy utilization.